Direct metal to metal bonding method for heterogenous 3D integration - Chua, Shen Lin (Nanyang Technological University, 2020)
Metal-based bonding will create vertical electrical connections between the dies and simultaneously create strong mechanical strength and hermetic sealing allowing heterogeneous 3D integration and 3D packaging. In this study, Cu-Cu fusion bonding with plasma surface modification and Al-Au thermocompression bonding were studied for reducing interconnect length, reducing pitch and increasing bandwidth for connection between top and bottom dies. Both methods of bonding used bonding and post-annealing temperature 300 ºC or less which is suitable for CMOS dies. Both methods also required shorter bonding time compared to Cu-Cu thermocompression while enabling batch annealing. Shear strength, electrical properties and hermetic sealing were investigated and demonstrated for enabling 3D integration and 3D packaging. Molecular structure and elemental composition for both methods of bonding were also studied and no voids were observed. Temperature cycling test from -40 to 125 ºC for 1,000 cycles were performed for Cu-Cu fusion bonding and mechanical shock test at 503.55g for 1.03 ms repeated 10 times were performed for Al-Au bonded samples to investigate bonding reliability.